Laparoscopic Versus Open Appendicectomy for Treatment of Acute Appendicitis (Journal of Surgical Sciences, 2019)
Laparoscopic appendicectomy is not yet considered the "gold standard" in the treatment of acuteappendicitis because of its higher operative time, intra-abdominal abscess risk, and costscompared to open appendicectomy. On the other hand laparoscopic appendicectomy is associatedwith fewer post operative complications, shorter hospital stay, and nearly similar operative time,intra-abdominal abscess rate, and total costs, compared with open appendicectomy. With increasein the experience of the surgeon in laparoscopic skills pit falls will be much lower. Therefore, laparoscopicappendectomy can be recommended as preferred approach in acute appendicitisJournal of Surgical Sciences (2016) Vol. 20 (1) : 24-25